Simulating herbage and soil organic carbon under Urochloa hybrid cv. Cayman in Tanzania using the Decision Support System for Agrotechnology Transfer CROPGRO-Perennial Forage Model - Korir, Mercy; Nyawira, Sylvia; Ordoñez, Leonardo; Boote, Kenneth; Paul, Birthe; Notenbaert, An; Hoogenboom, Gerrit (Cambridge University Press, 2025)
The Cropping System CROPGRO-Perennial Forage Model (CROPGRO-PFM) within the Decision Support System for Agrotechnology Transfer (DSSAT) framework is among the few models that simulate and evaluate perennial forages. However, its application to systems in East Africa remains limited. To address this gap, this study aimed to assess the capability of the CROPGRO-PFM model to predict herbage yield and soil organic carbon (SOC) dynamics under Urochloa hybrid cv. Cayman and to evaluate herbage and SOC responses to varying manure application rates in Tanzania. Model calibration involved adjusting parameters related to soil water content and the fraction of SOC in the stable pool. The simulated herbage yield showed a good agreement with observed data, with the D-statistic ranging from 0.58 to 0.85, with no calibration required from previous genotype coefficients used for Urochloa’s . The model captured seasonal variations in herbage production, showing peak yields during the wet season and reduced yields during the dry season. However, accurately capturing SOC variability requires long-term data, while our study was limited to just three years. Model application for 30 years across six sites revealed that a manure application rate of 10 t ha -1 led to SOC gains up to 0.7 Mg C ha -1 yr -1 and a 135% increase in herbage production. The results show the model’s potential application for simulating herbage yield and SOC under irrigation and manure management in East Africa.